2022
DOI: 10.3390/su14063380
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Sustainable Improvement of Educational Empirical Research Quality: What Kinds of Collaborative Production Relationships Make Sense?

Abstract: With the transformation of the knowledge production model, the research system of educational research is becoming more extensive, and academic collaboration has become an important productive method of promoting the sustainable development of educational empirical research. Given this situation, what kinds of relationships will sustainably improve educational empirical research output quality? Taking the influence of educational empirical research article as an example, we selected 4610 empirical research art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…and , respectively, then a reasonable estimate of is , which yields estimates of the direction of as follows: (15) estimator constructs the random matrix as follows:…”
Section: Study On the Synergistic Development Strategy Of Higher Voca...mentioning
confidence: 99%
See 1 more Smart Citation
“…and , respectively, then a reasonable estimate of is , which yields estimates of the direction of as follows: (15) estimator constructs the random matrix as follows:…”
Section: Study On the Synergistic Development Strategy Of Higher Voca...mentioning
confidence: 99%
“…By studying the impact of empirical educational articles as a basis for analysis, the study found that collaboration in identity, institution, and discipline all have a strong and significant impact on improving educational quality. Also, strengthening cooperation between general universities, optimizing the quality of international cooperation, and promoting the intersection of pedagogy with other disciplines is key to improving educational quality [15]. Altun, E constructs a model for overdispersed count data sets, analyzes the Poisson-Billar distribution and its associated two models,…”
Section: Introductionmentioning
confidence: 99%
“…The study found that collaboration in identity, institution, and discipline strongly and significantly impacts improving educational quality. Also, strengthening cooperation between general universities, optimizing the quality of international cooperation, and promoting the intersection of pedagogy with other disciplines is key to improving educational quality [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The experiment shows that the system is superior to other conventional methods. Literature [10] found that academic collaboration has become an important way to promote the sustainable development of educational research.…”
Section: Introductionmentioning
confidence: 99%